Spatial analysis of the role of women's capacity in the field of educational services in Raperin University - Ahmed, Asst.L.Roshna Mohammed; Mustafa, Asst.Prof.Dr.Fatima Qadir (Sulaimani Journal for Humanities, 2026)
Women have played an important role in all areas of society since ancient times, alongside men in writing, poetry, art, war, work, household management and the responsibility of educating future generations, even today There is no doubt that educated women have an important role in society, which reflects on personality, thinking, logic and education in society. Therefore, women play an important role in building society that cannot be ignored. The presence of women in higher education as teachers and researchers is considered important from the very beginning of their establishment, because women are an integral part of society and are considered the cornerstone of sustainable development. Because the benefits of women, especially in education and the qualifications they have obtained for their development and personality, broaden their perspectives and this enables them to fulfill their responsibilities in the field of education and service society. This research is about a geographical analysis of the role of women in the field of educational services, which discusses the role of women in Raperin University. The importance of this research is that it discusses an important topic, which is the role of women in the field of educational services in Raperin University. The aim of this study is to highlight the role of women in the field of educational services, as well as to highlight the detailed and scientific participation of women in the field of education in universities, while presenting the role of women alongside men in improving educational services Raperin.
Keywords: Women; Educational Services; Talent; Raperin University